Abundance determinations in the dIrr galaxy Leo A. Issue Volume 14:Issue S344(2019) (August 2018) - Ruiz-Escobedo, Francisco; Peña, Miriam; Hernández-Martínez, Liliana; García-Rojas, Jorge
Abstract: Physical conditions and chemical abundances of two H II regions and a planetary nebula in the dIrr galaxy Leo A are presented. These determinations were performed using the direct method (T e measured) and the ONS method. We also constructed photoionization models for the three nebulae to determine the abundances and to analyse the ionizing stars. The O abundance was determined to be 12+log(O/H) = 7.4±0.2 in all cases.